Use of plant growth regulators for yield improvement in coriander (Coriandrum sativum L.) - S S Rathore, B Singh, S N Saxena, R K Kakani, (Journal of Spices and Aromatic Crops, 2014)
Two genotypes of coriander viz., ACr 1 and RCr 41 were sown during rabi season in three consecutive years (2009–10, 2010–11 and 2011–12) and plant growth regulators (PGRs) viz., abscisic acid (ABA), betaine, acetyl salicylic acid (ASA) (1, 3, 5 and 7 μM) and proline (200, 400, 600 and 800 μM) were sprayed at flowering stage. Morphological parameters in terms of fresh: dry weight, shoot: root weight, shoot root length and seed yield was significantly increased by application of proline, betain and ASA from 1 to 7 μM. Effective concentration of PGRs was influenced by climatic conditions during growth period. In genotype ACr 1, yield was maximum (6.29 and 5.92 g plant-1) in the treatments involving betain at 1 and 5 μM while ASA at 3 and 5 μM resulted in seed yield of 4.96 and 4.97 g plant-1, respectively. Maximum seed yield (5.41 and 5.17 g plant-1) of genotype RCr 41 was recorded in the treatment involving proline at 200 and 400 μM, respectively. It is suggested that exogenous application of proline (200-800 μM), betain and ASA (1-5 μM) at flowering stage in both the genotypes will be useful to enhance the yield.